Daya Saing Permintaan Domestik Komoditas Industri Manufaktur di Lima Daerah Propinsi di Pulau Jawa - Zakaria, Junaiddin (Universitas Brawijaya, Indonesia, 2009)
The purpose of this research is to know competitive advantage of manufacturing industrial commodity of ready made clothes, leather and leather goods, paper and paper goods, of DKI Jakarta, West java, Central java, Yogykarta, and the East java. This research uses quantitative and qualitative approach using secondary data. The data was analyzed using modified Dong Sung Cho model to measure the competitive of domestic demand. The result of the research indicates that ready made Clothes industrial commodity group from Yogyakarta has fulfilled quality criterion, consequently has relative high copetitiveness at domestic demand. And West java it’s the second rank at domestic demand. East Java, Central Java and DKI Jakarta is the third rank, fourth rank, fiveth rank.. The industrial commodity of leather and leather goods of West Java has fulfilled quality criterion that consumers need, therefore has relatively high competitiveness at domestic demand, and Yogyakarta the second rank at domestic demand. While East Java, Central Java, and DKI Jakarta is the third rank, fourth rank, fiveth rank. The paper and paper goods industrial commodity from Yogyakarta has fulfilled quality criterion for domestic consumers, therefore has high competitiveness at domestic demand. West java has fulfil quality criterion but this commodity at second rank. While Central Java, East Java, DKI Jakarta is the third rank, fourth rank, fiveth rank.Keywords: Competitiveness Commodity, Manufacture Industry